Transforming growth factor β‐mediated micromechanics modulates disease progression in primary myelofibrosis. Issue 19 (5th September 2020) - Teodorescu, Patric; Pasca, Sergiu; Jurj, Ancuta; Gafencu, Grigore; Joelsson, Jon‐Petur; Selicean, Sonia; Moldovan, Cristian; Munteanu, Raluca; Onaciu, Anca; Tigu, Adrian‐Bogdan; Buse, Mihail; Zimta, Alina‐Andreea; et al.
Abstract: Primary myelofibrosis (PMF) is a Ph‐negative myeloproliferative neoplasm (MPN), characterized by advanced bone marrow fibrosis and extramedullary haematopoiesis. The bone marrow fibrosis results from excessive proliferation of fibroblasts that are influenced by several cytokines in the microenvironment, of which transforming growth factor‐β (TGF‐β) is the most important. Micromechanics related to the niche has not yet been elucidated. In this study, we hypothesized that mechanical stress modulates TGF‐β signalling leading to further activation and subsequent proliferation and invasion of bone marrow fibroblasts, thus showing the important role of micromechanics in the development and progression of PMF, both in the bone marrow and in extramedullary sites. Using three PMF‐derived fibroblast cell lines and transforming growth factor‐β receptor (TGFBR) 1 and 2 knock‐down PMF‐derived fibroblasts, we showed that mechanical stress does stimulate the collagen synthesis by the fibroblasts in patients with myelofibrosis, through the TGFBR1, which however seems to be activated through alternative pathways, other than TGFBR2.